TINJAUAN YURIDIS TERHADAP IMPLEMENTASI PIDANA KORUPSI DALAM UPAYA MENGEMBALIKAN KERUGIAN KEUANGAN NEGARA - Mustaghfirin Mustaghfirin; Irwanto Efendi (UNISSULA, 2015)
In Indonesia, the nature and form of corruption that has been systemic, thus making every effort to eradicate is not automatically easy to do just because of changes in democraticpolitical constellation. Corruption is closely related to the factor of abuse of authority or influence existing on the person’s position as an official who deviates from the law so that the action is detrimental to the state’s economy and finances. The act of corruption is complex as a complex crime is expressed by the increasingly sophisticated modus operandi used and the shrewdness of the perpetrators in removing traces makes the disclosure of corruption criminal cases increasingly difficult to reach, thus requiring a long time and a difficult way to provesufficiently juridically.Considering that Corruption has been classified as extraordinary crime so that in the effort of eradication and eradication it can no longer be done normally, but in extraordinary ways (Extra Ordinary Counter Measures) as described in general explanation of Law Number: 20 Year 2001 and Law Number: 30 Year 2002 about Corruption Eradication Commission. Necessary support of all components of the nation so that law enforcement officers need not hesitate to take action against anyone who commits a criminal act of corruption because the responsibility of eradicating corruption not only lies on the shoulders of law enforcer only, butalso the responsibility of all components of the nation.